Infaunal molting in Trilobita and escalatory responses against predation - Rustán, Juan José (2011)
The outstanding fossil record of trilobites contrasts with our limited knowledge of their lifestyles and strategies. Aspects such as infaunalism and behavioral defensive skills in this group have yet to be demonstrated conclusively. We report new insights based on a striking sclerite configuration exhibited by three phacopid trilobite species, part of a late Silurian-Early Devonian Paciphacops (Paciphacops) Maksimova, 1972, lineage. An unusual molt pattern provides compelling evidence of infaunal behavior, which accounts for a hiding, antipredatory adaptation. In addition, strengthening of the exoskeleton and acquisition of spines indicate an evolutionary trend toward morphological defensive strategies. Both trends in active and passive traits are considered escalatory in nature, thus providing unequivocal support for understanding the ecological role of trilobites as a main prey group in the context of the global diversification of predators recorded during middle Paleozoic time.